Foreign fighters : transnational identity in civic conflicts - Malet, David (New York : Oxford University Press, 2013)
'Foreign Fighters' is the comprehensive study of foreign fighters examines patterns of recruitment using original data sets and detailed diverse case studies, and how recruiters use frames of existential threat to strengthen rebel groups.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Apr. 30, 2013).
Keywords: Insurgency; Special forces (Military science)